MEDIA SOSIAL: HIPERREALITAS DAN SIMULACRA PERKEMBANGAN MASYARAKAT ZAMAN NOW DALAM PEMIKIRAN JEAN BAUDRILLARD - Minan Jauhari (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
This article provides affirmation or perhaps just an option in understanding the development of society today, some people call it a society of the era now that is identified with the informative society. It was acknowledged that the development of communication technology led to the use of social media that was quite massive, so that this technology was able to bring about the development of positive community actions and could accelerate the development of changes. However, some people understand that the development of this technology actually also brought the public to use social media to be alienated to him. No wonder the political style, social style, culture, and even various patterns show a more contemporary style. On this basis, this article provides an alternative to understanding critically the development of society nowadays which is identified as an information society. Is Jean Baudrillard, a post-structuralism thinker who first mentioned the existence of virtual possibilities in social media. So that the thoughts about Simulacra and Simulation that have been presented, are intended to be able to parse critically about the development of today's society.